Energy Transfer Studies of Electron Donating Carbazole and Electron Accepting Perylene Dye Systems - Shaban, Shaban Rajab (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Electron donating poly(2,7-carbazoles) are one of the most attractive materials emerged as p-type semiconductors for applications in photovoltaic devices in combination with relevant electron accepting systems. On the other hand, perylene dyes are known as versatile n-type building block materials for organic device architectures and supramolecular systems. These polymeric- or small molecule-based organic materials are very important concerning controlled and improved light emission is therefore a key issue and blending of fluorescent dye materials with conjugated polymers could enhance transfer of energy (excitation) from host to guest. In the present work, the electronic energy transfer between three different chromophoric materials of 2,7-carbazoles and perylene dyes were investigated. The carbazole compounds are considered as electron donors and perylene diimide is considered as electron accepting group. The energy transfer studies of three carbazole derivatives with perylene dye in three different kinds of varying polarity (CHCl3, 4.81; CH3CN, 37.5; CH3OH, 32.6) reveal that most efficiency is achieved for the three of the carbazoles in CHCl3. The critical transfer distances measured are in excellent agreement and in addition Stern-Volmer plots show efficient diffusion-controlled energy transfer in chloroform. Although there is no efficient nonradiative energy transfer in CH3CN and CH3OH, interesting charge transfer leading to electron transfer are evidenced from carbazole to perylene chromophore Keywords: Energy Transfer, Stern-Volmer, Carbazole, Perylene

ÖZ: Elektron verici poli(2,7-karbazoller), fotovoltaik cihaz uygulamalarında ilgili elektron alıcı sistemlerle kombinasyon halinde kullanılan p-tipi yarı iletkenler olarak ortaya çıkan en ilgi çekici maddelerdendir. Diğer yandan, perilen boyalar, organik cihaz mimarileri ve supramoleküler sistemler için çok yönlü bir n-tipi yapı taşı olarak bilinmektedir. Bu polimerik veya küçük molekül tabanlı organik maddeler gelişmiş ve kontrol edilebilir ışık emisyon özelliklerinden dolayı büyük önem kazanmaktadır. Bu nedenle, floresan boya malzemelerinin konjuge polimerlerle olan karışımları enerji transferinin artırılması açısından önemli bir konudur. Bu çalışmada, perilen boyaları ile üç farklı kromoforik 2,7-karbazol malzemleri arasındaki elektronik enerji transferi incelenmiştir. Karbazol bileşikleri elektron verici, perilen diimid ise elekron alıcı grup olarak kabul edilmiştir. Üç karbazol türevinin perilen diimid ile değişen polaritedeki çözgenlerde (CHCl3, 4.81; CH3CN, 37.5; CH3OH, 32.6) gerçekleştirilen enerji transfer çalışmalarında, üç karbazol türevi için de en etkili enerji transferi CHCl3 çözücüsünde sağlanmıştır. Ölçülen kritik transfer mesafeleri Stern-Volmer ilişkisine uygun olup, Stern-Volmer grafikleri kloroformda etkin difüzyon-kontrollü enerji transferi göstermektedir. CH3CN ve CH3OH çözgenlerinde etkin ışınımsız enerji transferi olmamasına rağmen, karbazolden perilen kromoforuna elektron transferine yol açan yük transferi gözlemlenmiştir. Anahtar Kelimeler: Enerji Transferi, Stern-Volmer, Karbazol, Perilen DICATION
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2013. Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Organic electronics; Energy Transfer; Stern-Volmer; Carbazole; Perylene